Method and appraisal in economics. - Latsis, Spiro J.; Λάτσης, Σπύρος Ι, 1946- (Cambridge, 1980)
Results from the Economics Sessions of the Nafplion Colloquium on Research Programmes in Physics and Economics held in Nafplion, Greece, 2-14 September, 1974.